PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOMOYO ICE CREAM & FRUIT TEA CABANG TUASAN - Diana Dongoran; Zulkarnain Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine and analyze the influence of brand image and product quality on consumers' purchasing decisions at Momoyo Ice Cream & Fruit Tea Tuasan Branch. The background of this research is based on fluctuations in sales transactions, observations indicating inconsistencies in product quality, and the results of a pre-survey showing that brand image, product quality, and consumers' purchasing decisions have not yet reached an optimal level. This research employed a quantitative approach using a survey method. The population consisted of all consumers of Momoyo Ice Cream & Fruit Tea Tuasan Branch, totaling 2,100 consumers. A sample of 100 respondents was selected using a purposive sampling technique based on the Slovin formula. Data were collected through questionnaires using a five-point Likert scale. The data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, partial significance testing (t-test), simultaneous significance testing (F-test), and the coefficient of determination (R²). The study proposed the hypotheses that brand image has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, and both brand image and product quality simultaneously have a positive and significant effect on consumers' purchasing decisions at Momoyo Ice Cream & Fruit Tea Tuasan Branch. The findings of this study are expected to provide valuable input for the company in improving its brand image and product quality to enhance consumers' purchasing decisions, as well as to serve as a reference for future research in the field of marketing management.